The new role of poly (rC)-binding proteins as iron transport chaperones: Proteins that could couple with inter-organelle interactions to safely traffic iron - Yanatori, Izumi; Richardson, Des R.; Toyokuni, Shinya; Kishi, Fumio (Biochimica et biophysica acta. General subjects, 2020)
Intracellular iron transport is mediated by iron chaperone proteins known as the poly(rC)-binding proteins (PCBPs), which were originally identified as RNA/DNA-binding molecules. PCBPs assume a role as not only as cytosolic iron carriers, but also as regulators of iron transport and recycling. PCBP1 is involved in the iron storage pathway that involves ferritin, while PCBP2 is involved in processes that include: iron transfer from the iron importer, divalent metal ion transporter 1; iron export mediated by ferroportin-1; and heme degradation via heme oxygenase 1. Both PCBP1 and PCBP2 possess iron-binding activity and form hetero/homo dimer complexes. These iron chaperones have a subset of non-redundant functions and regulate iron metabolism independently. This intracellular iron chaperone system mediated by PCBPs provide a transport “gateway” of ferrous iron that may potentially link with dynamic, inter-organelle interactions to safely traffic intracellular iron. •Intracellular iron is not found “free”, but is bound by iron chaperone proteins.•Iron chaperones include the multi-functional poly(rC)-binding proteins 1–4 (PCBPs).•PCBP1/2 play roles in iron metabolism, with the roles of PCBP3/4 being less clear.•The PCBPs bind 3 iron atoms and form hetero/homo dimer complexes.•PCBPs have a subset of non-redundant functions in iron metabolism.